SEASONAL VARIATIONS IN THE REPRODUCTION OF TWOSPOT CATFISH (Mystus nigriceps) FIN THE CICINGGULING RIVER, KEBUMEN, CENTRAL JAVA - Siti Rukayah; Agus Nuryanto; W Lestari; Isdy Sulistyo (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2026)
The Cicingguling River in Kebumen Regency is a freshwater ecosystem that serves as a critical habitat for native fish species, including Mystus nigriceps, which holds high ecological and economic value. This study aims to examine the reproductive characteristics of M. nigriceps over a full annual cycle (November 2022 - October 2023) using a survey method with purposive sampling. Field and laboratory sampling were conducted monthly to evaluate sex ratio, gonadal maturity stage (GMS), gonadosomatic index (GSI), fecundity, and egg diameter. The results showed an unbalanced sex ratio, with the number of female fish far exceeding that of males throughout the year. The GMS III and IV were higher during the rainy season, with GMS III at 295 individuals (female) and 170 individuals (male), and GMS IV at 259 individuals (female) and 144 individuals (male). The GSI and fecundity increased from December to February, coinciding with increased rainfall. The highest GSI and fecundity were recorded in January at 12.98% (females) and 6.63% (males), with fecundity reaching 17,927 eggs, accompanied by high rainfall (403 mm). Egg diameter during the rainy season showed a single peak (0.41–0.50 mm). In conclusion, M. nigriceps exhibits a seasonal reproductive pattern, indicating that the development of aquaculture and population dynamics depend on season-based management strategies. These findings provide a biological basis for data-driven conservation and support the sustainable management of freshwater fish resources in Central Java.